Advancing precision medicine through single‐cell sequencing: Insights and implications - Xu Zhang; Rongrong Gao; Liuke Yang; Youwei Zhu; Tiancheng Zhang; Xiaorong Shen; Wenwen Gu; Long Yang; Shenjie Peng (Wiley, 2024)
Abstract Background Single‐cell sequencing (SCS) marks the advent of a transformative period in biomedical studies, enabling unprecedented insight into the cellular intricacies of health and disease. Methods By dissecting the genetic, epigenetic and proteomic landscapes at the single‐cell level, SCS transcends traditional bulk sequencing methodologies, illuminating the heterogeneity and dynamics of individual cells. Results This analytical leap facilitates a deeper understanding of disease mechanisms, offers novel diagnostic and therapeutic targets and underpins the development of precision medicine across diverse fields such as neurology, oncology and immunology. Conclusions Despite its profound potential, SCS encounters challenges, including complex sample preparation, sophisticated data analysis and cost considerations. Nevertheless, ongoing advancements promise to overcome these barriers, integrating SCS with other omics data and leveraging machine learning to enhance biological understanding and clinical application. With the advancement of SCS technologies, personalised healthcare might be fundamentally altered, facilitating tailored and efficacious treatment strategies.